The beneficial therapeutic effects of plant‐derived natural products for the treatment of sarcopenia. Issue 6 (12th August 2022) - Bagherniya, Mohammad; Mahdavi, Atena; Shokri‐Mashhadi, Nafiseh; Banach, Maciej; Von Haehling, Stephan; Johnston, Thomas P.; Sahebkar, Amirhossein
Abstract: Sarcopenia is an age‐related muscle disorder typically associated with a poor quality of life. Its definition has evolved over time, and several underlying causes of sarcopenia in the elderly have been proposed. However, the exact mechanisms involved in sarcopenia, as well as effective treatments for this condition, are not fully understood. The purpose of this article was to conduct a comprehensive review of previous evidence regarding the definition, diagnosis, risk factors, and efficacy of plant‐derived natural products for sarcopenia. The methodological approach for the current narrative review was performed using PubMed, Scopus, and Web of Science databases, as well as Google Scholar (up to March 2021) in order to satisfy our objectives. The substantial beneficial effects along with the safety of some plant‐derived natural products including curcumin, resveratrol, catechin, soy protein, and ginseng on sarcopenia are reported in this review. Based on clinical studies, nutraceuticals and functional foods may have beneficial effects on physical performance, including handgrip and knee‐extension strength, weight‐lifting capacity, time or distance travelled before feeling fatigued, mitochondrial function, muscle fatigue, mean muscle fibre area, and total number of myonuclei. In preclinical studies, supplementation with herbs and natural bioactive compounds resulted in beneficial effects including increased plantaris mass, skeletal muscle mass and strength production, increased expression of anabolic factors myogenin, Myf5 and MyoD, enhanced mitochondrial capacity, and inhibition of muscle atrophy and sarcopenia. We found that several risk factors such as nutritional status, physical inactivity, inflammation, oxidative stress, endocrine system dysfunction, insulin resistance, history of chronic disease, mental health, and genetic factors are linked or associated with sarcopenia. The substantial beneficial effects of some nutraceuticals and functional foods on sarcopenia, including curcumin, resveratrol, catechin, soy protein, and ginseng, without any significant side effects, are reported in this review. Plant‐derived natural products might have a beneficial effect on various components of sarcopenia. Nevertheless, due to limited human trials, the clinical benefits of plant‐derived natural products remain inconclusive. It is suggested that comprehensive longitudinal clinical studies to better understand risk factors over time, as well as identifying a treatment strategy for sarcopenia that is based on its pathophysiology, be undertaken in future investigations.